(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article reflects the notion of in-between as the poetics of the theatrical event. From the performing arts and philosophy, the in-between is understood in this work as a web of bodies and the artistic event, acting as a relational force. The in-between is presented as conflict and contagion, but also as an extensive bridge and place both for the bodies (of actors and spectators) and for the theatrical event.